Analysis of a 15-years' experience in including shoulder muscles, when treating upper-limb spasticity post-stroke with botulinum toxin type A. Issue 3 (3rd April 2018) - Carvalho, Maria Pais de; Pinto, Daniela; Gorayeb, Melissa; Jacinto, Jorge
Abstract: Background: Botulinum toxin type-A (BoNTA) is a recognized treatment for upper limb spasticity (ULS) after stroke, but there aren't many studies analyzing its effect in shoulder muscles. Objective: To evaluate the efficacy of BoNTA injections for ULS, when shoulder muscles are included. Methods: A cross-sectional study. Data from clinical forms of outpatients, treated at a Rehabilitation Center (2001–2016). Analyzes: goals of treatment; demographic characteristics/goal; treatment success, using Goal Attainment Scaling. Results: Eighty-six stroke-patients, submitted to 547 BoNTA treatment sessions. The most injected shoulder muscles were subscapularis (SC) 35%, pectoralis major (PM) 31%, deltoideus 14%. The most selected goals for treatment were: involuntary movements (IM) 33%, pain/discomfort (PD) 26%, and mobility (MOB) 18%. Patients achieved or overachieved the IM goal in 76%, PD in 78%, and MOB in 79%. Patients with IM goal were younger ( p < 0.01), than those setting other goal types; PD patients, were older ( p < 0.019), treated half a year earlier ( p < 0.01), and had more spasticity (MAS ≠ 0.15); MOB patients were younger ( p = 0.04) and less spastic (MAS ≠ 0.12). Achieving PD goal impacted positively in improving MOB ( p = 0.042) and passive function ( p = 0.018). Conclusion: When treating ULS, including shoulder muscles, the most frequent goals were IM, PD e MOB. The most injected muscles were SC and PM. The treatment was successful in a large percentage of cases. Achieving the PD goal was associated with greater success at other goals of treatment. BoNTA demonstrated a positive effect in controlling symptoms and improving function.